My grandfather, the master detective - Konishi, Masateru, 1965- (G. P. Putnam's Sons, 2026)
A Japanese The Thursday Murder Club, taking healing fiction for a mystery-filled spin with this Japanese bestseller that has sold more than 200,000 copies in Japan. He's not your average Grandpa. As a lover of classic crime stories, it's no surprise that schoolteacher Kaede encounters everyday mysteries more often than your typical twenty-seven-year-old. Solving them is another matter, though. For that, she turns to her beloved grandfather, who retains a keen sharpness of mind despite his dementia, and who was once a key member of The Waseda Mystery Club. From impossible locked room murders to confounding missing persons cases, the grandfather-granddaughter duo "weave stories" to get to the bottom of every mystery. But all the while, an insidious shadow from Kaede's past slowly closes in on her . . . Steeped in references to classic crime from Christie to Chesterton to Poe, My Grandfather, the Master Detective plays with the genre, capturing readers' imagination in this Tokyo-set escapist mystery. Its charming characters and affectionate focus on relationships echo heartwarming Japanese titles such as Before the Coffee Gets Cold. --